Impairments of Visuospatial Attention in Children with Unilateral Spastic Cerebral Palsy. (17th December 2018) - Ickx, Gaétan; Hatem, Samar M.; Riquelme, Inmaculada; Friel, Kathleen M.; Henne, Camille; Araneda, Rodrigo; Gordon, Andrew M.; Bleyenheuft, Yannick
Abstract : Aim . This observational study aimed at assessing the prevalence of visuospatial attention deficits in children with unilateral spastic cerebral palsy (USCP), taking into consideration the affected hemibody and the localization of the brain lesion. Method . Seventy-five children with USCP were assessed with four visuospatial attention tests: star cancellation, Ogden figure copy, line bisection, and proprioceptive pointing. Results . A majority (64%) of children with USCP presented a deficit in at least one test compared to the reference values. The alterations observed in children with left or right USCP were related to egocentric or allocentric neglect, respectively. Children with cortico/subcortical lesion presented more often visuospatial attention deficits than children with periventricular lesion. Visuospatial attention deficits were not associated with brain lesion locations. Interpretation . Visuospatial attention deficits are prevalent in children with USCP and should be taken into account during their rehabilitation process. The present results shed new light on the interpretation of motor impairments in children with USCP as they may be influenced by the frequent presence of visuospatial deficits.